Diagnostic Aspects of Veterinary and Human Aspergillosis - Elad, Daniel; Segal, Esther (Frontiers in Microbiology, 2018)
The genus Aspergillus is composed of more than 300 species, a fraction of which are involved in animal or human infections mostly following environmental exposure. Various risk factors (i.e. immunosuppression, tuberculosis) have been recognized for human whereas for veterinary infections, unhygienic management, trauma, anatomical conformation of the skull or suspected immunological deficiencies, have been suggested. In animals, aspergillosis is mostly sporadic but in some circumstance such as infections on poultry farms, may involve the whole flock. Since the high prevalence of immunosuppression in human patients has not been mirrored in veterinary medicine, and although to the best of our knowledge, no comprehensive data on the prevalence of aspergillosis in animals has been published, their epidemiology has not changed during the last decades. The impact of these infections may be economic or if they are incurable, sentimental. The objective of the first part is to describe the diagnosis of the main clinical entities caused by Aspergillus spp. in animals. It includes disseminated canine aspergillosis, canine and feline sino-nasal and sino-orbital aspergillosis, guttural pouch mycosis in horses, mycotic abortion in cattle, mycotic keratitis in horses and avian aspergillosis. When pathogenesis and clinical aspects are relevant for diagnosis – they will be addressed as well. The second part deals with human aspergillosis, which is a multifaceted disease, manifested in a spectrum of clinical entities affecting one or more organs. Diagnosis is based on the clinical manifestation, supported and confirmed by laboratory means, involving the classical approach of demonstrating the etiological agent in the clinical specimens and in culture. Noncultural methods, such as antigen detection and/or molecular assays to detect fungal nucleic acids or protein profiles, are used as well. The isolation and identification of the fungus allows the determination of its susceptibility to antifungal drugs. Thus, antifungal susceptibility testing maybe considered as part of the diagnostic process, which is of relevance for management of the infection. In this review article, the part dealing with diagnostic aspects of aspergillosis in humans concentrates on susceptibility testing of Aspergillus spp. to antifungal drugs and drug-combinations. The technologies and methods of susceptibility testing are described and evaluated.